PENGARUH PELAYANAN ADMINISTRASI AKADEMIK DAN IKLIM ORGANISASI TERHADAP KEPUASAN MAHASISWA FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH TANGERANG - Panggabean, Swandi; Kamil, Mustofa; Mulyadi, Edi (Perspektif : Jurnal Ilmu Administrasi, 2020)
The title of this Research is the Influence of Academic and Clinical Administration Service of the Organization to the Student Satisfaction of Faculty of Health Sciences at Muhammadiyah University of Tangerang. This research was conducted at the Faculty of Health Sciences University of Muhammadiyah with the object of the researchers are all students of the Faculty of Health Sciences Muhammadiyah University of Tangerang. The purpose of this study is to analyze the influence of Academic and Clinical Administrative Services on Student Satisfaction Faculty of Health Sciences Muhammadiyah University of Tangerang. Research is a quantitative study using the method of causal survey, this method uses path analysis (goal analysis) whose purpose is to determine the effect of service Academic administration, and organizational climate with student satisfaction of Faculty of Health Sciences UMT. In order to answer the above problem formulation, this study was conducted with the total population of 528 students, samples taken as many as 228 students by distributing questionnaires to respondents. From the results of research conducted showed that there is a significant influence between academic administration services with student satisfaction with coefficient value 0.801, and there is significant influence between organizational climate to student satisfaction with coefficient value 0.733; And there is a simultaneous influence between academic administration services and organizational climate on student satisfaction.Keywords: Academic administration services, organizational climate, student satisfaction.